Application of human induced pluripotent stem cell-derived cardiomyocytes sheets with microelectrode array system to estimate antiarrhythmic properties of multi-ion channel blockers - Hiroko Izumi-Nakaseko; Mihoko Hagiwara-Nagasawa; Atsuhiko T. Naito; Ai Goto; Koki Chiba; Yuko Sekino; Yasunari Kanda; Atsushi Sugiyama (Journal of Pharmacological Sciences, 2018)
We examined electrophysiological indices of human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) sheets in order to quantitatively estimate Na+, K+ and Ca2+ channel blocking actions of bepridil and amiodarone using microelectrode array system in comparison with that of E-4031. We analyzed the field potential duration, effective refractory period, current threshold and conduction property using a programmed electrical stimulation protocol to obtain the post repolarization refractoriness and coefficient a of the relationship between the pacing cycle length and field potential duration. Electropharmacological profile of each drug was successfully characterized; namely, 1) the changes in the current threshold and conduction property provided basic information of Na+ channel blocking kinetics, 2) the relationship between pacing cycle length and field potential duration reflected drug-induced inhibition of human ether-à-go-go-related gene (hERG) K+ channel, 3) the post repolarization refractoriness indicated the relative contribution of these drugs to Na+ and K+ channel blockade, and 4) L-type Ca2+ channel blocking action was more obvious in the field potential waveform of the hiPSC-CMs sheets than that expected in the electrocardiogram in humans. Thus, this information may help to better utilize the hiPSC-CMs sheets for grasping the properties and net effects of drug-induced Na+, Ca2+ and K+ channel blockade. Keywords: Human induced pluripotent stem cell-derived cardiomyocytes, Post repolarization refractoriness, Multichannel blocker, Antiarrhythmic property